Conditions affecting production of functional muscle recombinant alpha-tropomyosin in Saccharomyces cerevisiae - Alegria, M. C.; Lavarda, SCS; Lataro, R. C.; Hilario, E.; Ferro, J. A.; Bertolini, Maria Celia [UNESP] (Elsevier B.V., 2003)
Yeasts are attractive hosts for heterologous protein production as they follow the general eukaryotic post-translational modification pattern. The well-known Saccharomyces cerevisiae has been used to produce a large variety of foreign proteins. The proper function of muscle tropomyosin depends on a specific modification at its N-terminus. Although tropomyosin has been produced in different expression systems, only the recombinant protein produced in the yeast Pichia pastoris has native-like functional properties. In this paper we describe the production of functional skeletal muscle tropomyosin in the yeast S. cerevisiae. The recombinant protein was produced in high amounts and production was strongly affected by genetic and environmental factors, including plasmid copy number, promoter strength, and growth media composition. (C) 2003 Elsevier B.V. (USA). All rights reserved.